Differential behavior patterns in cynomolgus monkey Macaca fascicularis in home cage in response to human gaze. Issue 1 (2nd December 2014) - Zou, Hong; Luan, Yi; Liu, Ming; Agre, Lynn A.; Buyske, Steven; Xie, Qinglian; Cheng, Zhiheng; Zhao, Guoping; Jin, Meilei; Guo, Ning; Jin, Gang Jason; Yu, Lei
Abstract Background Non‐human primates, when encountering human beings, show wariness and alertness. These behaviors differ when there is direct human gaze vs. when human averts his gaze. Methods We observed cynomolgus monkey in their home cage and studied their behaviors in response to human gaze. Four behaviors were analyzed: opening mouth, staring at observer, agitated activity, and approaching observer. Results Three behaviors appeared to be sensitive to human gaze between when the human observer gazed at the monkey and when the human observer looked away. Individual animals also displayed subpatterns of responses to human gaze. Conclusions These results indicate that, even in their home cage, monkeys display a heightened level of awareness when gazed upon by a human observer, suggesting that human gaze may elicit emotional reactions. Further, under the human gaze, distinct behavioral subpatterns were apparent within the monkey cohort in our study, indicative of subgroups within the cohort.